1996
DOI: 10.1021/jp9516001
|View full text |Cite
|
Sign up to set email alerts
|

Oscillation of Membrane Potential in Chemically Modified Poly(α-amino acid) Membranes

Abstract: Chemically modified poly(γ-methyl-L-glutamate) membranes having several lengths of diamine segments generated oscillation of membrane potential under a concentration gradient of several salts, although nonmodified membranes showed constant potential. The oscillation of membrane potential is considered to be caused by the fluctuation of the fixed charge density originating from the thermal fluctuation of partially ionized amine segments in the modified membranes. The amplitude of the oscillation was greater in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…The oscillation of the membrane potential in the ionÈcomplex membranes of DNA and hexamethylenediamine can be expected to be generated at pH 7.0 which is a more natural condition compared to pH 10.0 in the previous study. 19 The recognition of the salt present in the solution is also investigated from the amplitude and the power spectra of fast Fourier transform during the oscillation of the membrane potential. This observation may contribute to a simple model of the processing method for the recognition of taste and smell found in animal brains.…”
mentioning
confidence: 99%
“…The oscillation of the membrane potential in the ionÈcomplex membranes of DNA and hexamethylenediamine can be expected to be generated at pH 7.0 which is a more natural condition compared to pH 10.0 in the previous study. 19 The recognition of the salt present in the solution is also investigated from the amplitude and the power spectra of fast Fourier transform during the oscillation of the membrane potential. This observation may contribute to a simple model of the processing method for the recognition of taste and smell found in animal brains.…”
mentioning
confidence: 99%
“…By seeking such chemical oscillation system, some researchers achieved artificial nonlinear oscillators such as BZ reaction, permeation phenomena of membrane, rhythmic drug delivery systems, and so on. [1][2][3][4][5] However, only one work has achieved an artificial oscillatory system induced by molecular recognition, the important feature of living body. [6] Meanwhile, our group has succeeded in developing polymeric material exhibiting a coordination of molecular recognition and actuation function within the polymer itself.…”
Section: Introductionmentioning
confidence: 99%
“…The Belousov-Zhabotinsky reaction [11][12][13] is widely known in such phenomena and was explained by the Field-Koros-Noyas mechanism. 14 Several kinds of artificial membranes [15][16][17][18][19][20][21][22][23][24] which induce the oscillation of the membrane potential have also been reported as simple models of cells and living membranes. Most of the studied artificial membranes [15][16][17][18][19] are bimolecular lipid or liquid membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies deal with the electrical oscillatory phenomena in artificial polymeric membranes. [20][21][22][23][24] Huang and Spangler 21 studied a poly(glutamic acid)-Ca 2+ membrane in order to clarify the dynamic behavior of the electrical oscillation. Minoura et al 22 observed the spontaneous oscillation of the electrical membrane potential in a triblock copolypeptide membrane separating KCl solutions of different concentrations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation